IMPLEMENTASI KEBIJAKAN PUBLIK PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 - Hidayat, Firman; Heriyanto, Meyzi; Firdaus, Firdaus (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Public Policy of Riau Province Regional Regulation Number 6 of 2012. This study aims to evaluate the effectiveness of the implementation of Riau Provincial Regulation No. 6 of 2012 concerning Corporate Social Responsibility in Riau Province. This research is descriptive and explorative qualitative research. The research informants were the Dumai City Government bureaucracy, the Industry and Trade Office, the company and the community in Dumai, Buluh Kasab and Datuk Laksamana. Data collection techniques are interviews, observation and documentation. Data analysis uses interactive models through the process of data reduction, data display and conclusion drawing or data verification. From the results of the study it was found that the implementation of the Riau provincial government policy on the Corporate Social Responsibility and the Environment was not effective.